When crowding‐in and when crowding‐out? The boundary conditions on the relationship between negative online reviews and online sales. (15th December 2021) - Shen, Ao; Wang, Peng; Ma, Yongyuan
Abstract : Drawing on the motivation crowding theory, we propose a novel framework concerning the moderating effects of customer‐initiated reviews and merchant‐initiated replies on the relationship between negative online reviews and online sales performance. Using 14, 096 online reviews collected from Meituan.com, we found that the detrimental effect of negative online reviews will be mitigated with a greater level of customer‐initiated reviews and a medium level of merchant‐initiated replies. This study enhances the current understanding of the dyadic interaction between online customers and offline merchants, thereby suggesting the crowding‐in and crowding‐out effects of the merchant online replies toward negative online reviews.